KAJIAN MUTU BIJI KAKAO PETANI DI KABUPATEN LUWU TIMUR, SOPPENG DAN BULUKUMBA - Sabahannur, St; Nirwana, Nirwana; Subaedah, St (Jurnal Industri Hasil Perkebunan, 2016)
The research objective is to assess physical and sensory quality of dried cocoa beans producedin Bulukumba, Soppeng, and East Luwu Regions. The research was conducted by taking samples ofcocoa directly from farmers of those three districts, as the cocoa producer regions in South SulawesiProvince. The physical quality of the samples was examined in accordance with SNI 2323-2008 and forsensory testing, the samples were sent to Puslitkoka, Jember for flavor and aroma. Data analysis wascarried out using descriptive statistical analysis. The result shows that the beans from those three regionsdo not meet the standard of SNI 2323-2008 for water content, slaty beans, level of foreign objects andinsects, while the level of free fatty acid ranges from 1.02 â 1.65%. Total fat content of cocoa beans fromBulukumba region, higher than the others, is 35.74% and the pH level for all samples are neutral (6.47 â6.78). The result of sensory test shows that cocoa beans from Bulukumba region have astringent flavor,those from Soppeng region have very niceflowery flavor, and those from East Luwu shows half-fermentedcocoa beans and chocolate medium.Keywords: cocoa beans, physical quality, aroma, flavor